Sleep quality and preclinical Alzheimer Disease - Ju, Yo-El S. (2013)
OBJECTIVE: Sleep and circadian problems are very common in Alzheimer Disease (AD). Recent animal studies suggest a bidirectional relationship between sleep and amyloid-β (Aβ), a key molecule involved in AD pathogenesis. This study tested whether Aβ deposition in preclinical AD, prior to the appearance of cognitive impairment, is associated with changes in quality or quantity of sleep. METHODS: Cognitively normal, middle-aged individuals (n=142) had sleep objectively measured using actigraphy for 2 weeks. Concurrent sleep diaries provided nap information. Cerebrospinal fluid Aβ42 levels were used to determine whether amyloid deposition was present or absent. Sleep parameters were assessed with regard to amyloid deposition. RESULTS: Amyloid deposition was associated with worse sleep quality, specifically worse sleep efficiency (% time in bed that was spent asleep), compared to those without amyloid deposition. In contrast, quantity of sleep was not different between groups, as measured by total sleep time. Frequent napping was associated with amyloid deposition. INTERPRETATION: Amyloid deposition in the preclinical stage of AD appears to be associated with worse sleep quality, but not with changes in sleep quantity.